Pengembangan Creative Organic di Kawasan Permukiman Kelurahan Langkai Kota Palangka Raya - Hamidah, Noor; Nindito, Dwi Anung; Syahrozi, Syahrozi; Santoso, Mahdi; Kamariah, Nurul Asma; Albalaqoti, Irhas; Pradipta, Aria (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Utilizing footbridges and yards on the Kahayan Riverside area, Langkai Village as an initial idea in efforts to fulfill food security. Footbridges and yards are used as media where daily vegetable and fruit crops can be planted. Vegetables and fruit fulfill daily needs and provide special skills for children at Islamic boarding schools. The location of the Islamic boarding school in Palangka Raya City is located on the riverside area, this inspired the idea of ​​growing fruit and vegetables on the Kahayan. River side area to provide food supplies. The service aims to stimulate the children (Students) of Madradah Tsanawiyah Hidayatul Insan to use the walkways and yards as areas for growing fruit and vegetables. The location of the service is located at the Hidayatul Insan Islamic Boarding School on the Kahayan Riverside area, Langkai Village. The method used was a qualitative method based on interviews with Islamic boarding school supervisors, discussions regarding types of fruit and vegetable plants, and planting fruit and vegetables using hydroponic cultivation media by Madrasah Tsanawiyah (MTs) Hidayatul Insan students. Activities of the Community Empowerment Assistant Lecturer Program Team (PDPPM) FT UPR have provided assistance starting from the preparation stage, implementation stage, and until the stage of harvesting the plants. The results of the service are that MTs students can identify types of plants, are able to choose plants, plant and care for plants using hydroponic media, in line with the idea of ​​service, namely creative organic